Territorial Economic Intelligence and the Competitiveness of CSR-Labeled SMEs: What Relationship? - MALLOU , Salma; AIT LEMQEDDEM , Hamid (Revue Internationale des Sciences de Gestion, 2025)
This article explores the dynamic relationship between territorial economic intelligence (TEI) and the CSR labeling of small and medium-sized enterprises (SMEs). We highlight the mechanisms of TEI that enable SMEs to collect, analyze, and utilize strategic information about their local environment while underscoring the competitive advantages that CSR labeling can bring. Through a comprehensive analysis, we examine how TEI influences the strategies of SMEs, particularly those that have achieved CSR labels, and assess the potential synergies that emerge from this interaction. Ultimately, this reflection leads to the proposal of a conceptual model illustrating this relationship, along with hypotheses examining the link between TEI and the strategic development of enterprises. The findings emphasize the importance of an integrated approach to encourage the adoption of CSR within SMEs and to enhance their competitiveness in an increasingly sustainability-focused market.